EAST AFRICAN COMMUNITY'S TRADE POTENTIAL AND PERFORMANCE WITH EUROPEAN UNION: A PERSPECTIVE OF SELECTED FRUIT AND VEGETABLE COMMODITIES - Moses Lubinga; Abiodun Ogundeji; Henry Jordaan (European Scientific Journal, ESJ, 2014)
Based on the impressive growth trend within the export-driven horticulture sector over the past 2-3 decades among the East African Community (EAC) member states, this paper aims at predicting the trade potential and performance of a selected fruits and Vegetables (FVs) within the European market. Within the gravity model framework, based on the Zero Inflated Poisson (ZIP) estimator, we use the out-of sample approach to predict potential trade flows of FVs by using highly disaggregated panel data. In light of ascertaining trade performance of EAC member states' FV commodities within the EU market, we use the Relative Difference index. Empirical results reveal that Asparagus from Kenya has room for trade expansion across all the EU-member states while Beans and pepper from Uganda also have a large un-exploited market within the EU market. Similarly, Beans from Tanzania also have room for trade expansion across many EU member states. Results further revealed that EAC member states exhibit poor trade performance within the EU-market in the various FV commodities, which suggests that there exists some barriers to trade between the EAC and EU. Thus, it is incumbent upon EAC member states to foster trade cooperation in horticultural commodities with the EU member states.